Pengaruh British Exit (Brexit) Terhadap Kebijakan Pemerintah Inggris Terkait Masalah Imigran - Hardi Alunaza SD; Virginia Sherin (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2018)
This paper aims to explain the influence of British Exit (Brexit) on the UK government's policy on immigrants. The results of the referendum on June 23, 2016, show that more than fifty two percent of Britons choose to leave the EU. The UK's exit from EU membership affects some of the policies of the British government, in particular, the policy on immigrants. However for immigrants, the new policy to be implemented by the British government is considered as a threat. This article uses the theory of policy making and the concept of immigration with qualitative research method in the form of literature study. This paper shows that the impact of Brexit on the UK government's policy on immigrants is the discourse of limiting the number and selection of immigrants that will affect both British and immigrant communities.